Cheating on Unproctored Internet Test Applications: An Analysis of a Verification Test in a Real Personnel Selection Context. (3rd December 2018) - Aguado, David; Vidal, Alejandro; Olea, Julio; Ponsoda, Vicente; Barrada, Juan Ramón; Abad, Francisco José
Abstract: This study analyses the extent to which cheating occurs in a real selection setting. A two-stage, unproctored and proctored, test administration was considered. Test score inconsistencies were concluded by applying a verification test (Guo and Drasgow Z-test). An initial simulation study showed that the Z-test has adequate Type I error and power rates in the specific selection settings explored. A second study applied the Z-test statistic verification procedure to a sample of 954 employment candidates. Additional external evidence based on item time response to the verification items was gathered. The results revealed a good performance of the Z-test statistic and a relatively low, but non-negligible, number of suspected cheaters that showed higher distorted ability estimates. The study with real data provided additional information on the presence of suspected cheating in unproctored applications and the viability of using item response times as an additional evidence of cheating. In the verification test, suspected cheaters spent 5.78 seconds per item more than expected considering the item difficulty and their assumed ability in the unproctored stage. We found that the percentage of suspected cheaters in the empirical study could be estimated at 13.84%. In summary, the study provides evidence of the usefulness of the Z-test in the detection of cheating in a specific setting, in which a computerized adaptive test for assessing English grammar knowledge was used for personnel selection.